STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF LANGUAGE DAY AT DORMITORY OF MADRASAH MUALLIMIN MUHAMMADIYAH YOGYAKARTA - Rudianto (PBI 15 UMY 03, 2015)
*3 Language day is a day when the students speak Arabic or English language in every single activity for a whole day at the dormitory (Ahada, 2012). Language day has been implemented at the multilingual dormitory of Madrasah Muallimin Muhammadiyah Yogyakarta more than six years. Unfortunately, language day, which has been implemented more than six years, is not evaluated yet. As a result, the researcher was interested in discovering and analyzing the perception from the students regarding to the implementation of language day. What problems found in the implementation of language day are. The research was carried out through six representative students from two different locations of the dormitory of Muallimin. The main finding of this research shows language day is good to be implemented at dormitory because language day makes the students more creative in language. Moreover, the implementation of language day at dormitory improves students’ communication competence and students’ speaking skill. Another finding, there are five problems found in the implementation of language day. The main problem is that the students are being unfamiliar with foreign and there is no serious control by the teachers in the implementation of language day at dormitory. Finally, this research suggests that this research can be considered as the evaluation for the teacher and institution on the implementation of language day at dormitory.